Board performance and firm performance of Malaysian listed companies - Kamardin, Hasnah; Haron, Hasnah (Inderscience Publishers, 2011)
This study explores the roles of the board of directors (BOD) (as a proxy for board performance) in Malaysian listed companies and examines the relationship between board roles and firm performance.Four board roles (strategy, service, monitoring, and resource dependence) are considered in this study.Questionnaires are used to ascertain the extent of the BOD participation in the board roles in the financial year 2006.The sample of the study is 109 directors, which represents a 20.96% response rate.The results of the component factor analysis produce six roles. The strategy and service roles remain as one factor but monitoring and resource dependence has been refactorised into two categories. Results of the regression analysis between board roles and firm performance found that management oversight roles are positively related to ROA and Tobin's Q, which supports the need to have greater management oversight in companies characterised by concentrated ownership in enhancing the shareholders' wealth. The negative relationship between protecting shareholders' interests and ROA and between strategy and dependency on the expertise of outside directors and Tobin's Q are not consistent with the agency theory and resource dependency theory.